2020
DOI: 10.1002/jcp.30026
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: HDAC2‐mediated proliferation of trophoblast cells requires the miR‐183/FOXA1/IL‐8 signaling pathway

Abstract: Pre‐eclampsia (PE) is a major cause of maternal and perinatal death. Previous research has indicated the role of histone deacetylase 2 (HDAC2) in the pathogenesis of PE but the relevant molecular mechanisms are unknown. However, there is hitherto little information concerning the molecular mechanism behind HDAC2 in PE. Herein, we hypothesized that HDAC2 promotes trophoblast cell proliferation and this requires the involvement of microRNA‐183 (miR‐183), forkhead box protein A1 (FOXA1), and interleukin 8 (IL‐8).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 44 publications
3
8
0
Order By: Relevance
“…In addition, another research unveiled that HDAC2‐targeting shRNA caused suppression of the in vitro migration and invasion ability of colorectal cancer cells, which was concordant with our finding 16 . Also, ectopic expression of HDAC2 could lead to facilitation of the proliferation, migration and invasion of human trophoblast cells HTR‐8/SVNEO 17 …”
Section: Discussionsupporting
confidence: 89%
“…In addition, another research unveiled that HDAC2‐targeting shRNA caused suppression of the in vitro migration and invasion ability of colorectal cancer cells, which was concordant with our finding 16 . Also, ectopic expression of HDAC2 could lead to facilitation of the proliferation, migration and invasion of human trophoblast cells HTR‐8/SVNEO 17 …”
Section: Discussionsupporting
confidence: 89%
“…The miR-183-96-182 cluster is well known to be a typical miRNA cluster because its three components have similar seed sequences and common target genes, and even play similar biological functions [10,14]. In the present study, we demonstrated that the miR-183-96-182 cluster members may share a common promoter, which is activated by the same Increasing evidence suggests that the miR-183-96-182 cluster has a common putative promoter in humans [4,30,35,36]. The miR-183-96-182 cluster members were coupregulated or co-downregulated in β -Cateninoverexpressing or β-Catenin-silencing cells; mechanically, β-Catenin directly binds to the putative promoter located in −8000 nt ~−6000 nt of 5 regulatory region of the miR-183-96-182 cluster and thereby activates the transcription of this cluster in AGS cells [30] and hepatocellular carcinoma cells [31].…”
Section: Discussionsupporting
confidence: 62%
“…The miR-183-96-182 cluster members were coupregulated or co-downregulated in β -Cateninoverexpressing or β-Catenin-silencing cells; mechanically, β-Catenin directly binds to the putative promoter located in −8000 nt ~−6000 nt of 5 regulatory region of the miR-183-96-182 cluster and thereby activates the transcription of this cluster in AGS cells [30] and hepatocellular carcinoma cells [31]. Furthermore, some transcription factors such as STAT5 [37], MYCN [38], ZEB1 [39], and KLF4 [40], and several epigenetic modulators such as HDAC2 [36,38] have been shown to interact with the putative promoter of the miR-183-96-182 cluster to positively or negatively regulate its transcription and function. Here, we further showed that the miR-183-96-182 cluster members may share a common promoter and a common transcription activator SMAD4 in pigs.…”
Section: Discussionmentioning
confidence: 99%
“…First, it has been validated that TF FOXA1 can induce the expression of target genes CD274 and IL8 by directly binding to their promoter region [ 124 , 125 ]. It is worth noting that the MIR183/FOXA1/CXCL8 pathway activated by HDAC2 has been investigated in a previous study [ 126 ]. In Figure 4 , we show that this pathway is, instead, mediated by TF ZEB1 and incorporated with the downstream of the TGFβ signaling pathway.…”
Section: Resultsmentioning
confidence: 99%